Comparison of superovulatory responses to a standardized hormonal superstimulation protocol among three indigenous breeds of sheep in Brazil - Pupin, Maria Amélia Ferrão [UNESP]; Oliveira, Maria Emilia Franco [UNESP]; Vergani, Gabriel Brun [UNESP]; Lima, Monalisa Sousa Dias; Silva, Kleibe de Moraes; Monteiro, Alexandre Weick Uchôa; Ramos, Alexandre Floriani; Batista, Ribrio Ivan Tavares Pereira; Souza-Fabjan, Joanna Maria Gonçalves; Bartlewski, Pawel Mieczyslaw; Fonseca, Jeferson Ferreira (Elsevier, 2022)
This study examined the differences in ovarian responses and in vivo embryo production in three naturalized Brazilian sheep breeds (Morada Nova, Santa Inês, and Somalis Brasileira). Thirty cycling, multiparous ewes (n = 10/breed) received intravaginal devices containing 0.33 g of progesterone (CIDR®) for 9 days and the twice-daily superovulatory treatment with 133 mg of porcine follicle-stimulating hormone (six decreasing doses) started on Day 7 (Day 0 PM = CIDR® insertion). On Days 11 (36 h after CIDR® removal) and 15 (12 h before non-surgical embryo recovery performed seven days after CIDR® removal), all ewes were examined using B-mode and Doppler ultrasonography. The number of medium-sized ovarian follicles (4.0–5.99 mm) on Day 11 was greater (P = 0.003) in Santa Inês and Somalis Brasileira compared with Morada Nova ewes. Small antral follicle numbers (2.0–3.99 mm in diameter) on Day 11 were directly related to ovulatory responses in all three breeds of superovulated ewes. The number of corpora lutea on Day 15 was greater (P < 0.0001) in Santa Inês, followed by Somalis Brasileira and Morada Nova ewes; however, the number of viable embryos and viability rate did not differ (P > 0.05) among the three genotypes of ewes studied. The total ovarian area (TA), color Doppler area (DA), and DA/TA × 100% increased from Day 11 to Day 15 in all breeds, and they were lowest (P < 0.001) in superovulated Morada Nova sheep. Significant positive correlations among ovarian antral follicle numbers in different size classes (Day 11) and ovulatory responses were recorded in all breeds, but associations between the ovarian blood perfusion and superovulatory outcomes were restricted to the Morada Nova and Santa Inês genotypes. In summary, ovarian follicle numbers and blood flow indices differed among the three naturalized Brazilian ewes, but no significant differences were noted in embryo yields and quality following superovulation. Small antral follicle count 36 h after CIDR® treatment was a reliable predictor of impending ovulation rates in all ewes under study.
Keywords: Color Doppler; Corpora lutea; Ewe; Ovarian antral follicles; Ovarian blood perfusion; Superovulation